The management of clinically early ovarian cancer patients who have not undergone staging surgery - Kaban, Alpaslan; Ferlengez, Ayşe Gül; Kaban, İşık (Journal of Surgery and Medicine, 2019)
Four-thirds of patients with epithelial ovarian cancer are diagnosed at an advanced stage, and the main choice of treatment is primary cytoreductive surgery followed by adjuvant platinum-based chemotherapy, or interval surgery after neoadjuvant chemotherapy in patients who are not eligible for optimal cytoreductive surgery. In patients with disease clinically confined to the ovary, The International Federation of Gynecology and Obstetrics (FIGO) recommends comprehensive staging to detect the real stage of the disease, but some these patients do not undergo staging during operation. Retrospective studies in the literature report that re-operation, adjuvant chemotherapy without re-operation or observation are some of the management options during the postoperative period for patients with clinically early stage disease. In this article, the management of these patients was reviewed in light of the current literature.